Relative familial clustering of cerebral versus coronary ischemic events. - Banerjee, A; Silver, L; Heneghan, C; Welch, S; Mehta, Z; Banning, A; Rothwell, P (2011)
BACKGROUND: Few population-based studies have ascertained both cerebral and coronary events or considered their relative heritability. Differences in heritability of transient ischemic attack and ischemic stroke versus acute coronary syndromes (ACS) may inform risk prediction, genetic studies, and understanding of disease mechanisms. METHODS AND RESULTS: In a population-based study of all acute vascular events, irrespective of age, we studied family history of myocardial infarction (MI), stroke, and related risk factors in first-degree relatives. To allow for differences in rates of affected first-degree relatives caused by differences in disease incidence, we looked at the extent to which parental history was associated with affected siblings within disease category. Nine hundred six probands (604 men; mean age, 70 years) with ACS and 1015 (484 men; mean age, 73 years) with cerebral events had complete family history data. In ACS probands, parental MI was associated with MI in ≥1 sibling (1 parent with MI: odds ratio, 1.48; 1.04 to 2.10; P=0.03; both parents with MI: odds ratio, 5.97; 3.23 to 11.03; P<0.0001). In probands with cerebral events, however, parental stroke was not associated with sibling stroke. The overall frequency of ≥2 siblings with the same condition was also greater in probands with ACS than in those with cerebral events (odds ratio, 5.43; 3.03 to 9.76; P<0.00001), despite similar overall incidence of MI and stroke in our study population. One hundred forty-two (15.7%) cases of ACS occurred in families with ≥2 affected first-degree relatives compared with 56 (5.1%) transient ischemic attack/strokes. All results were similar when analyses were confined to probands with MI only versus stroke only, and independent of smoking. CONCLUSIONS: Heritability of coronary events was greater than that of cerebral events, such that MI was more likely to cluster in families than was stroke.